HUBUNGAN KESADARAN METAKOGNITIF DENGAN KEMAMPUAN MEMAHAMI NILAI-NILAI YANG TERKANDUNG DALAM TEKS HIKAYAT - Gani, Rifchan; Ramandhanti, Dina; Tatalia, Ricci Germani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Learning hikayat texts at the high school level aims to shape students' character through understanding life values. One of the contributing factors is low metacognitive awareness, namely students' ability to manage, monitor, and evaluate thought processes while reading. This study aims to determine the relationship between metacognitive awareness and the ability to understand values in hikayat texts of grade X Phase E students of SMA Pertiwi 1 Padang. This study uses a quantitative approach with a correlational method. The study population was all grade X Phase E students of SMA Pertiwi 1 Padang in the 2024/2025 academic year. A sample of 30 people was determined using a simple random sampling technique. Data collection was carried out using two instruments, namely a metacognitive awareness questionnaire and a multiple-choice test to measure understanding of values in hikayat texts. The results of data analysis showed that the level of students' metacognitive awareness was in the high category with an average percentage of 71.50%. Meanwhile, students' ability to understand the values of the fable text is also classified as high with an average value of 81.53. The results of the Pearson correlation test show a positive and significant relationship between metacognitive awareness and the ability to understand the values of the fable text, as evidenced by the calculated t value > t table (2.11 > 1.70).